Facile fabrication of mechanically robust flexible asymmetric supercapacitors based on mesh electrode. (20th September 2022) - Song, Ya; Yang, Huawei; Bai, Liangjiu; Chen, Hou
Abstract: In this paper, a free-standing and robust asymmetric flexible supercapacitor was developed using electrodeposited MnO2 and MoS2 /Fe2 O3 on carbon cloth (CC) and molybdenum mesh (MM) as positive and negative materials, respectively, and neutral LiCl/polyvinyl alcohol hydrogel as the gel electrolyte. The supercapacitor achieved an operating voltage window of up to 2.0 V and an excellent areal capacitance of 727.1 mF cm −2 at 1 mA cm −2, which delivered outstanding energy and power densities of 101 μWh cm −2 and 0.502 mW cm −2, respectively. Moreover, benefitting from the complementary mechanical properties of the two substances, the as-prepared flexible supercapacitor has the characteristics of high-strength and excellent resistant to bending, which maintained almost unchanged capacitance when bent to an arbitrary angle. The flexible supercapacitor has the potential of being a high-performance energy storage device with a simple preparation, high cost efficiency, and environmentally friendly properties.